Methanolobus halotolerans sp. nov., isolated from the saline Lake Tus in Siberia. Issue 10 (11th October 2020) - Shen, Ya; Chen, Sheng-Chung; Lai, Mei-Chin; Huang, Hsing-Hua; Chiu, Hsiu-Hui; Tang, Sen-Lin; Rogozin, Denis Yu; Degermendzhy, Andrey G.
Abstract : A halotolerant, psychrotolerant and methylotrophic methanogen, strain SY-01 T, was isolated from the saline Lake Tus in Siberia. Cells of strain SY-01 T were non-motile, cocci and 0.8–1.0 µm in diameter. The only methanogenic substrate utilized by strain SY-01 T was methanol. The temperature range of growth for strain SY-01 T was from 4 to 40 °C and the optimal temperature for growth was 30 °C. The pH range of growth was from pH 7.2 to 9.0, with optimal growth at pH 8.0. The NaCl range of growth was 0–1.55 M with optimal growth at 0.51 M NaCl. The G+C content of the genome of strain SY-01 T was 43.6 mol % as determined by genome sequencing. Phylogenetic analysis revealed that strain SY-01 T was most closely related to Methanolobus zinderi SD1 T (97.3 % 16S rRNA gene sequence similarity), and had 95.5–97.2 % similarities to other Methanolobus species with valid names. Genome relatedness between strain SY-01 T and DSM 21339 T was computed using average nucleotide identity and digital DNA–DNAhybridization, which yielded values of 79.7 and 21.7 %, respectively. Based on morphological, phenotypic, phylogenetic and genomic relatedness data presented here, it is evident that strain SY-01 T represents a novel species of the genus Methanolobus, and the name Methanolobus halotolerans sp. nov. is proposed. The type strain is SY-01 T (=BCRC AR10051 T =NBRC 113166 T =DSM 107642 T ).